Upaya Komisi Pemilihan Umum (Kpu) Kota Pontianak dalam Mewujudkan Partisipasi Masyarakat yang Demokratis pada Pemilihan Umum Tahun 2024 - Qadri, Ul; Awaluddin, M.; YM, Adiyath Rendy (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
The General Election Commission of Pontianak City, West Kalimantan Province, stated that the voter participation rate for the 2019 election in Pontianak city was 81.4 percent or an increase compared to the 2014 election, which was only 72 percent. Voter participation in the 2019 elections in Pontianak City has increased by more than 9 percent. This increase also increased compared to the 2018 simultaneous local elections, which was 75 percent. The purpose of this study is to find out what efforts have been made by the Pontianak City Election Commission in realizing democratic community participation. The objects of this research are the KPU of Pontianak City and the people who have voting rights. The research method used is qualitative with descriptive data encoding. Collecting data using interviews, observation and documentation. The results of the study show that the Pontianak City Election Commission carries out socialization and formal and informal approaches to the community. Apart from that, we also utilize social media and the KPU website to provide understanding regarding the importance of exercising the right to vote and receiving public complaints via the KPU website or coming directly to the Pontianak City General Election Commission office.